Superior photo-carrier diffusion dynamics in organic-inorganic hybrid perovskites revealed by spatiotemporal conductivity imaging - Xuejian Ma (Nature Portfolio, 2021)
Spatiotemporal dynamic of charge carriers is commonly studied with optical or photoconductivity measurements, yet these techniques come with their own limitations. To circumvent these limits, the authors probe the free-carrier diffusion dynamics of microsecond lifetimes via laser-illuminated microwave impedance microscopy.